Wisdom and Courage. Issue 10 (15th September 2018) - Hack, Laurita M
Abstract: Laurita M. (Laurie) Hack, DPT, PhD, MBA, FAPTA, has contributed to the physical therapy profession as an educator, researcher, and academic leader (Fig. 1 ). Dr Hack is Professor Emeritus in the Department of Physical Therapy at Temple University in Philadelphia, Pennsylvania. An independent consultant in physical therapy research and education, she also serves on the adjunct faculty in the Department of Physical Therapy at Arcadia University, Glenside, Pennsylvania. Dr Hack holds a BA from Wilmington College; an MS as the first professional degree in physical therapy from Case Western Reserve University; an MBA from the Wharton School, University of Pennsylvania; a PhD in higher education administration from the University of Pennsylvania; and a DPT from the MGH Institute of Health Professions. Dr Hack has clinical experience in outpatient, nursing home, and home care practice, especially in geriatrics, and has taught in the areas of practice management, geriatrics, clinical decision making, evidence-based practice, ethics, and health care systems. Her research interests include development of clinical expertise, the physical therapy workforce, and physical therapy education. She is a coauthor of Expertise in Physical Therapy Practice and of Evidence Into Practice. She is a coinvestigator in the grant, Physical Therapist Education for the Twenty First Century (PTE-21): Innovation and Excellence in Physical Therapist Education. Dr Hack has served the American Physical Therapy Association (APTA) as president of the Home, Health Section, the Health Policy & Administration Section, and the Education Section (now the Academy of Physical Therapy Education) and the Education Section (now the Academy of Physical Therapy Education), and as vice speaker and secretary of the APTA Board of Directors. Her APTA honors include being named a Catherine Worthingham Fellow of APTA, the Lucy Blair Service Award, and the Baethke-Carlin Award for Teaching Excellence.